The Use of CRISPR/Cas9 as a Tool to Study Human Infectious Viruses - Lin, Huafeng; Li, Gang; Peng, Xiangwen; Deng, Aimin; Ye, Lei; Shi, Lei; Wang, Tuanmei; He, Jun (Frontiers in Cellular and Infection Microbiology, 2021)
Clustered regularly interspaced short palindromic repeats (CRISPR) systems are a set of versatile gene-editing toolkit that performs diverse revolutionary functions in various application fields such as agricultural practices, food industry, biotechnology, biomedicine and clinical research. Specially, as a novel antiviral method of choice, CRISPR/Cas9 system has been extensively and effectively exploited to fight against human infectious viruses. Infectious diseases including human immunodeficiency virus (HIV), hepatitis B virus (HBV), human papillomavirus (HPV) and other viruses are still global threats with persistent potential to probably cause pandemics. To facilitate virus removals, the CRISPR/Cas9 system has already been customized to confer new antiviral capabilities into host animals either by modifying host genome or by directly targeting viral inherent factors in the form of DNA. Although several limitations and difficulties still need to be conquered, this technology hold great promises in the treatment human viral infectious diseases. In this review, we will firstly present a brief biological features of CRISPR/Cas9 systems, which including a description of CRISPR/Cas9 structure and composition, then we focus on the investigations and applications that employing CRISPR/Cas9 system to combat several human infectious viruses, and discuss challenges and future perspectives of using this new platform in the preclinic and clinic as an antiviral strategy.